Tetracyclic thioxanthene derivatives: Studies on fluorescence and antitumor activity - Durães, F (2021)
Thioxanthones are bioisosteres of the naturally occurring xanthones. They have been described for multiple activities, including antitumor. As such, the synthesis of a library of thioxanthones was pursued, but unexpectedly, four tetracyclic thioxanthenes with a quinazoline– chromene scaffold were obtained. These compounds were studied for their human tumor cell growth inhibition activity, in the cell lines A375-C5, MCF-7 and NCI-H460. Photophysical studies were also performed. Two of the compounds displayed GI50 values below 10 µM for the three tested cell lines, and structure–activity relationship studies were established. Three compounds presented similar wavelengths of absorption and emission, characteristic of dyes with a push-pull character. The structures of two compounds were elucidated by X-ray crystallography. Two tetracyclic thioxanthenes emerged as hit compounds. One of the two compounds accumulated intracellularly as a bright fluorescent dye in the green channel, as analyzed by both fluorescence microscopy and flow cytometry, making it a promising theranostic cancer drug candidate.